Increasing Empathy, Decreasing Prejudice: The Role Of Empathy In Challenging Prejudice Among Students - Heaton, Adam P (Innovare Journal of Education, 2022)
Is empathy a remedy for prejudice? This short paper argues it has a large role to play. It explores the authors’ observations as a Humanities teacher engaging Grade 8 Australian students between the ages of 12 and 14 in a study of the film Rabbit-Proof Fence. As students empathised with Aboriginal (Indigenous Australian) children forcibly removed from their families under Australian government policy in the twentieth century, they questioned the negative things they themselves had come to believe about Indigenous Australians.